Влияние ассортимента мелющих тел в мельницах барабанного типа на эффективность разрушения измельчаемого материала при помоле - Баранов, А. Н.; Морозов, А. И. (НТУ "ХПИ", 2006)
Розглянуто питання контакту куль, що мелють, і часток матеріалу, що подрібнюють в кульових млинах, з позицій теорії удару. Розроблено модель оцінки напруг, що виникають у частках матеріалу при ударі куль. Розроблена модель дозволяє оптимізувати розмір і швидкість куль, що мелють, у процесі помелу матеріалу у кульових млинах.

The questions of the contact of the milling solids and particles of the material which reduced in ball-mills of the blow theory position are considered. The model of the strains estimation which appears in the particles of the material under the balls blow is designed. The designed model allows to optimizing the size and the velocity of the passage in the process of the material grinding in the ball-mills.
Keywords: механическое измельчение; частицы материала; шаровая мельница; процесс помола; мелющее тело; деформация